أثر التغطية الأرضية البلاستيكية والأنفاق المنخفضة في الإنتاج المبكر لمحصول الكوسا Cucurbitapepo .L - عيسى, ريم; بوراس, متيادي; زيدان, رياض (Latakia University Journal -Biological Sciences Series, 2014)
نفذ البحث في مشتل جامعة تشرين على الهجين Nancy F1 من الكوسا في العروة الربيعية للموسم الزراعي 2013 لدراسة أثر التغطية الأرضية والأنفاق المنخفضة في الإنتاج المبكر لمحصول الكوسا. شملت الدراسة أربع معاملات تجريبية مكونة من : شاهد (بدون تغطية )،وثلاث معاملات تغطية تضمنت تغطية أرضية بالبلاستيك الأسود ، وتغطية أرضية بالبلاستيك الأسود +نفق بلاستيكي منخفض ، ونفق بلاستيكي منخفض من دون تغطية أرضية.اعتمد تصميم العشوائية الكاملة بثلاثة مكررات للمعاملة الواحدة ، وبمعدل10 نباتات في المكرر. أظهرت النتائج أن التغطية بالأنفاق البلاستيكية المنخفضة تفوقت على باقي المعاملات وأدت إلى زيادة واضحة في عدد الأزهار المؤنثة ،نسبة الأزهار المؤنثة /الكلية ، عدد الثمار على النبات، إنتاج النبات وإنتاجية وحدة المساحة. كماأشارت النتائج إلى وجود علاقة ارتباط إيجابية قوية بين إنتاج النبات وكل من عدد الأزهار المؤنثة (r=0.999)، وعدد الثمار على النبات (r=0.999)، ونسبة الأزهار المؤنثة /الكلية (r=0.990)،وعدد الأزهار الكلية (r=0.995)، بينما كانت العلاقة سلبية مع عدد الأزهار المذكرة (r=-0.954). The research was conducted on hybrid Squash (Nancy F1) at Tishreen University in the growing season of spring 2013 in order to study the effect of ground covering and low tunnels on the early production of squash. The study consisted of four experimental treatments: the control (without covering) and three covering treatments (ground covering using black mulch, ground covering with a low plastic tunnel, and a low plastic tunnel without ground covering). The completely randomized design was used with three replications per treatment and ten plants per replication. The results showed that the covering with a low plastic tunnel was superior to other treatments, resulting in a clear increase in female flowers, the ratio of female flowers to the total flowers, fruit number, and plant production. The results also showed a strong positive correlation between the plant production and the number of female flowers (r=0.999), the number of fruit per plant (r=0.999), the ratio of female flowers to the total flowers (r=0.990) and the total number of flowers (0.995). The correlation with male flowers was however negative (r=-0.954).